2011
DOI: 10.3892/ol.2011.416
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of breast cancer cells to taxol by inhibition of taxol resistance gene 1

Abstract: Abstract. The purpose of this study was to determine the role of taxol resistance gene 1 (TXR1) in a taxol-resistant breast cancer cell line. Expression levels of TXR1 and thrombospondin-1 (TSP1) were detected by RT-PCR and Western blot analysis. In MCF-7 cells transfected with TXR1 plasmids, the expression of a number of drug resistance genes was monitored, as well as cell proliferation. MCF-7 cells were also transiently transfected with a chemically synthesized small interfering RNA (siRNA) targeting TXR1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Lih et al 7 have demonstrated that increase in TXR1 and decrease in TSP1 expression was highly correlated with taxane resistance in cancer cells. Bai et al 16 showed that TXR1 expression was associated with a resistant phenotype of breast cancer cells in vitro. However, it remains unknown whether TXR1 and TSP1 expression correlates with the outcome of breast cancer patients who receive taxane-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lih et al 7 have demonstrated that increase in TXR1 and decrease in TSP1 expression was highly correlated with taxane resistance in cancer cells. Bai et al 16 showed that TXR1 expression was associated with a resistant phenotype of breast cancer cells in vitro. However, it remains unknown whether TXR1 and TSP1 expression correlates with the outcome of breast cancer patients who receive taxane-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Papadaki et al 15 also demonstrated that low TXR1 and high TSP1 expression was an independent factor for increased PFS docetaxel-based first-line chemotherapy in patients with advanced/metastatic non-small-cell lung cancer. In breast cancer MCF-7 cells, Bai et al 16 showed that increased expression of TXR1 was associated with a taxol-resistant phenotype.…”
mentioning
confidence: 99%
“…SiRNAs are a class of small synthetic double-stranded RNAs which can induce gene silencing through sequence-specific cleavage of perfectly complementary mRNA [ 86 ]. In the last decades, the potential of siRNA-based therapy in cancer treatment has determined a huge concentration of studies and led to promising results on the inhibition of cancer cell growth and migration and the enhancement of drug response [ 87 , 88 , 89 , 90 , 91 , 92 ]. Recently, many investigators have focused their efforts on the use of siRNA-based therapy to reprogram the TME and alter the crosstalk between stromal and cancer cells [ 93 , 94 , 95 , 96 , 97 , 98 ] ( Table 3 ).…”
Section: Synthetic Rna-based Therapeutic Approaches For Caf Targetmentioning
confidence: 99%
“…Txr1 is a drug resistance gene receiving increasing attention; this gene decreases thrombospondin-1 (TSP1) secretion and causes taxol resistance ( 8 ). Previous studies using lung ( 9 ) and breast ( 10 ) cancer cells have revealed that Txr1 upregulation may induce drug resistance in cancer cells. Our previous study revealed that Txr1 expression is also associated with the 5-year overall survival (OS) rate of GC patients and may represent a target to reverse L-OHP resistance in GC ( 11 ).…”
Section: Introductionmentioning
confidence: 99%